Anti-Inflammatory Eﬀect of Pimpinella anisum Extract in a Mouse Model of Allergic Asthma - Tahereh Dargahi; Reza Ilkhani; Azadeh Ghiaee; Roya Arbabtafti; Shirin Fahimi; Seyyed Shamsadin Athari; Fatemeh Jafari; Hanieh Kashafroodi; Rasool Choopani* (Iranian Society of Pharmacognosy, 2021)
Background and Objectives: Allergic asthma is a chronic inflammatory disease of the airways which has become prevalent globally. There are reports about the immunomodulatory and antioxidant effects of Pimpinella anisum L. seeds; so, in this study, we explored the suppressive effects of aqueous P. anisum L. seeds extract on ovalbumin-induced asthma in a mouse model. Methods: The seeds were extracted with water and the extract was dried by freeze-drying method. Twenty-eight BALB/c male mice weighing 15-20 g were divided into four groups of seven animals. Ovalbumin was used to trigger allergic asthma in these animals. Negative and positive control mice received phosphate-buffered saline and ovalbumin, respectively. The remaining two groups were challenged with ovalbumin and then received budesonide and the seed extract, respectively. Thereafter, the eosinophils count and expression of IL-5, -13, and -33 were measured in bronchoalveolar lavage fluid of mice. Histopathological changes of the lung tissues were also analyzed. Results: Aqueous extract of P. anisum seeds hindered ovalbumin -stimulated asthmatic complications by declining eosinophils number and expression of IL-5, -13, and -33 in bronchoalveolar lavage fluid of mice. It also inhibited the hyperplasia of goblet cells, hypersecretion of mucus, and inflammation in peribronchial and perivascular spaces, which were consequences of ovalbumin exposure. The activity of the extract in suppressing inflammatory responses of asthma in our murine model was comparable to budesonide. Conclusion: Our data underscored the effect of aqueous P. anisum seeds on the suppression of inflammatory responses of allergic asthma, proposing a promising suggestion for the treatment of the disease.